1997
DOI: 10.1046/j.1365-294x.1997.t01-1-00202.x
|View full text |Cite
|
Sign up to set email alerts
|

The problem of sampling families rather than populations: relatedness among individuals in samples of juvenile brown trout Salmo trutta L.

Abstract: In species exhibiting a nonrandom distribution of closely related individuals, sampling of a few families may lead to biased estimates of allele frequencies in populations. This problem was studied in two brown trout populations, based on analysis of mtDNA and microsatellites. In both samples mtDNA haplotype frequencies differed significantly between age classes, and in one sample 17 out of 18 individuals less than 1 year of age shared one particular mtDNA haplotype. Estimates of relatedness showed that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(167 citation statements)
references
References 14 publications
4
162
0
Order By: Relevance
“…Early (soon after hatching) non-random kin associations have been demonstrated in other stream fishes, including Atlantic salmon (Salmo salar) (Olsen et al 2004;Einum and Nislow 2005), brown trout (Salmo trutta) (Hansen et al 1997;Hansen and Jensen 2005;Carlsson 2007;Sanz et al 2011) and high predation populations of guppies (Poecilia reticulata) (Piyapong et al 2011) and are likely to be demonstrated in future studies of additional species. Population-specific spatial variation in kin associations is likely to vary with environmental conditions and age of the individuals under consideration.…”
Section: Discussionmentioning
confidence: 85%
“…Early (soon after hatching) non-random kin associations have been demonstrated in other stream fishes, including Atlantic salmon (Salmo salar) (Olsen et al 2004;Einum and Nislow 2005), brown trout (Salmo trutta) (Hansen et al 1997;Hansen and Jensen 2005;Carlsson 2007;Sanz et al 2011) and high predation populations of guppies (Poecilia reticulata) (Piyapong et al 2011) and are likely to be demonstrated in future studies of additional species. Population-specific spatial variation in kin associations is likely to vary with environmental conditions and age of the individuals under consideration.…”
Section: Discussionmentioning
confidence: 85%
“…If fish remain in the vicinity of their hatching location until maturity (see for example, Allendorf and Phelps, 1981;Hansen et al, 1997), most individuals collected in those two small lakes could likely be derived from a small number of progenitors only. Mating could then be biased toward relatives if most dispersal opportunities are restricted to the close surroundings of the lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically haplotypes 1, 18, 22 and 23 were present only in the Monterivoso population and could represent the pool of the putative native mtDNA haplotypes (see also Caputo et al 2004). The existence of a separate cluster containing three haplotypes (upper cluster of figure 2) mainly occurring in the Irish population, and the fact that just three of them were previously observed in Danish populations (Hansen & Loeschcke 1996;Hansen et al 1997), suggest the non-Danish origin of the entire Atlantic stocks implied in the Central-Western Italy restocking. The existence of such restocking practice with allochthonous stock is confirmed by LDH-C1* analysis, which reveals the presence of several hybrids showing the characteristic Atlantic allele (Table II).…”
Section: Discussionmentioning
confidence: 84%